(3QSGdI fRgI GdebJSW aj ChVGY GdeNeS NGdi GdhSWs - (3YHO Gddg Hf eMeO Hf YHO Gdedc, CHh eMeO GdeQLGfj,J (B699 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3abO SCdfi HYV ENhGfi Cf CVY dge JbjjOkG s
(3BNQgG (B:s
(3bdJ dGHO ef eTGQcg TjN fGUM hEdG hbY GdZdW s
(3Vef eLehY , JQJjHgG (B: (3ef U (B126 - (3U(B141s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B130s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B927 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B57 s
(3eUOQ GbJfGA GdCUd (B:s
(3Mcje ChZdh (B(607(2)) s
Keywords: (3Gdadcs